Effects of Whole-Body Electromyostimulation versus High-Intensity Resistance Exercise on Body Composition and Strength: A Randomized Controlled Study - Kemmler, Wolfgang; Teschler, Marc; Weißenfels, Anja; Bebenek, Michael; Froehlich, Michael; Kohl, Matthias; von Stengel, Simon (Evidence-based complementary and alternative medicine, 2016)
High-intensity (resistance) exercise (HIT) and whole-body electromyostimulation (WB-EMS) are both approaches to realize time-efficient favorable changes of body composition and strength. The purpose of this study was to determine the effectiveness of WB-EMS compared with the gold standard reference HIT, for improving body composition and muscle strength in middle-aged men. Forty-eight healthy untrained men, 30-50 years old, were randomly allocated to either HIT (2 sessions/week) or a WB-EMS group (3 sessions/2 weeks) that exercised for 16 weeks. HIT was applied as "single-set-to-failure protocol," while WB-EMS was conducted with intermittent stimulation (6 s WB-EMS, 4 s rest; 85 Hz, 350 ms) over 20 minutes. The main outcome parameters were lean body mass (LBM) as determined via dual-energy X-ray absorptiometry and maximum dynamic leg-extensor strength (isokinetic leg-press). LBM changes of both groups (HIT 1.25 ± 1.44% versus WB-EMS 0.93 ± 1.15%) were significant (p = .001); however, no significant group differences were detected (p = .395). Leg-extensor strength also increased in both groups (HIT 12.7 ± 14.7%, p = .002, versus WB-EMS 7.3 ± 10.3%, p = .012) with no significant (p = .215) between-group difference. Corresponding changes were also determined for body fat and back-extensor strength. Conclusion. In summary, WB-EMS can be considered as a time-efficient but pricy option to HIT-resistance exercise for people aiming at the improvement of general strength and body composition.
EVALuna2:33288